Technology Roadmap for Industry 4 - Sarvari, Peiman Alipour; Ustundag, Alp; Cevikcan, Emre; Kaya, Ihsan; Cebi, Selcuk (SPRINGER-VERLAG LONDON LTD, 2018)
From both strategic and technologic perspectives, the Industry 4.0 roadmap visualizes every further step on the route towards an entirely digital enterprise. In order to achieve success in the digital transformation process, it is necessary to prepare the technology roadmap in the most accurate way. The intent of this chapter is to present a technology roadmap for Industry 4.0 transformation to facilitate the planning and implementation process.
Keywords: STRATEGIC MANAGEMENT; Engineering